Modelling and simulation for autonomous systems : second International Workshop, MESAS 2015, Prague, Czech Republic, April 29-30, 2015, revised selected papers /: second International Workshop, MESAS 2015, Prague, Czech Republic, April 29-30, 2015, revised selected papers. (2015) - Unknown
No abstract available